대기질 입체감시를 위한 항공측정 플랫폼 구축 - 서범근(Beom-Keun Seo); 박수복(Soo bog Park); 이도영(Doyoung Lee); 유명상(Myeongsang Yu); 유정훈(Jeonghun Yu); 배귀남(Kwi-Nam Bae); 안준영(Joonyoung Ahn); 박진수(Jinsoo Park); 김세웅(Saewung Kim); 이태형(Taeyoung Lee); 김종호(Jongho Kim) (한국대기환경학회지(국문), 2019)
At present, the well-equipped aircraft is the mostly sought-after research platform to measure both the vertical and spatial distributions of air quality parameters. In this study, Beechcraft B1900D was custom configured and modified for continuous and constant-flow samplings of aerosol and gaseous species mainly within planetary boundary layer. The aircraft has a maximum takeoff weight of 7,765 kg with 1,984 kg maximum payload and maximum power output of 22.4 kW. Two iso-kinetic aerosol inlets were designed and mounted on the roof of aircraft fuselage. Four gas inlets were mounted on each side of fuselage in ahead of aircraft wings. Currently, aircraft is capable for simultaneous installation of various instruments including HR-ToF-AMS, PTR-ToF-MS, CIMS, major reactive gas analyzers with up to six operators. Recent test flight indicated that the performance of newly adapted sampling systems in this aircraft was suitable for future intensive airborne observations. KCI Citation Count: 0